Haemophilia A in a Patient with Testicular Feminization - Andrejev, Yu. N; Korenevskaya, M. I; Rutberg, R. A; Dukarevitch, M. Z; Pokrovskiy, P. I; Tokarev, Yu. N (Thrombosis and Haemostasis, 1975)
A case of typical haemophilia A in phenotypically “hairless” woman aged 18 with complete testicular feminization (primary amenorrhea, absence of palpated gonads, negative sex chromatin, fluorescence of Y chromosome in interphase nuclei, caryotype 46, XY by common and fluorescent methods) is reported in this paper. Both diseases are of familial character with transmission through female line. The propositus’ father did not suffer from haemophilia. Signs of Morris syndrome (delay of menses, absence of secondary hair) are present in the propositus’ mother and sister. The propositus’ niece, the daughter of her sister, also suffered from testicular feminization, but without any haemophilia, probably due to the crossing-over. The analysis of the pedigree gives no information in favour of sex-linked or autosome-dominant sex limited inheritance of testicular feminization. Haemophilia A in the propositus is characterized by the very low factor-VIII level – 1.66%, and typical joints bleedings since 3 years. At the age of 18 the patient had major surgery for a haemophilic thigh pseudotumor. There was rapid consolidation of the fracture and contracture was erradicated. In spite of severe factor VIII deficiency the course of haemophilia in the propositus is clinically milder than in male haemophiliacs in her family and in the general population.The similar findings were reviewed in literature including the case of hemyzygous haemophilia with testicular feminization and described women-homozygotes. The suggestion is made that the course of haemophilia in the propositus is affected by the female phenotype. The psychological status of the patient and the possibility of professional rehabilitation by surgical treatment is discussed. The need for detailed cytogenetical examination of the persons with “female” haemophilia or the other sex-linked diseases to establish the correct diagnosis and for exclusion of the possible mosaicism is discussed.